Determination of growth, leaf yield, quality and safety of potted Ocimum gratissimum L. cultivated using different fertilizer types - Nneka Angela Okoli; Elozonachukwu Stella Maris Udoh; Chukwudi Michael Lambert (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The purpose of the study was to produce compost and compare the effect with other fertilizer types on scent leaf vegetative growth, yield, nutrient contents and heavy metal accumulation for safety of consumers.